A rare cause of upper airway obstruction: spontaneous synchronous sublingual and laryngeal haematomas. (3rd May 2011) - Parvizi, Sahar; Mackeith, Samuel; Draper, Mark
Abstract : Anticoagulation with warfarin is commonly used for prevention of thromboembolic events in patients with atrial fibrillation. Bleeding is the main side effect of anticoagulation. We report the case of a 66-year-old man who developed two spontaneous synchronous upper airway haematomas while on warfarin therapy. To our knowledge, this is the first reported case of a sublingual haematoma presenting simultaneously with supraglottic laryngeal haematomas. Upper airway haematomas are rare in the absence of a history of trauma but need to be urgently assessed due to their life-threatening potential. Clinicians should be aware of the possibility of haematomas involving the upper airway in patients on anticoagulant therapy, particularly if complaining of red flag symptoms such as acute onset dysphonia, odynophagia or airway/breathing difficulties.